ANALYSIS OF COFFEE CONSUMER SATISFACTION AT “KEDAI BENTO” IN SOLO, SALATIGA, AND YOGYAKARTA BRANCH - Retna Dewi Lestari; Intan Lukita Sari Intan; Octaria Nur R; Zainul Muttaqin (Proceeding of International Conference on Science, Health, And Technology, 2022)
This study aims to determine the attributes that are considered important by consumers in order to achieve customer satisfaction, determine the level of satisfaction or the level of consumer suitability for products and services at Kedai Bento Kopi, and determine the attributes that need to get priority from the company to be improved in order to achieve this. customer satisfaction. This research was conducted at the Bento Coffee Shop. The sample used is 44 respondents using purposive sampling method. Data obtained by distributing questionnaires and correspondence directly. This research uses a descriptive method. The results of this study indicate that the product quality attributes that are considered important are sorted from large to small: coffee flavor formulation, coffee taste balanced between bitter, sweet, and sour, consistent coffee taste in every serving. The level of service quality performance is sorted by attributes with the highest percentage level being employees providing drink recommendations when consumers are confused in choosing a menu. The highest level of consumer satisfaction with product quality: Attributes Consumers prefer to enjoy drinks in cold conditions with a percentage of (56.4%) and the smallest attribute at an affordable coffee bento price which is 16.3%, and the presentation of Bento Coffee products is 27, 3%.